2020
DOI: 10.1108/ijqrm-11-2019-0349
|View full text |Cite
|
Sign up to set email alerts
|

Let's get everyone involved! The effects of transformational leadership and organizational culture on organizational excellence

Abstract: PurposeThis paper posited a dynamic relationship between transformational leadership, organizational culture, and organizational excellence in order to develop a better understanding of the casual linkages between these three areas.Design/methodology/approachThe research methodology includes a multi-item scale questionnaire survey which included 448 samples from United Arab Emirates (UAE) with an average response rate of 61.1%. The hypotheses were tested by applying structural equation modeling (SEM) and path … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
0
7

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(64 citation statements)
references
References 90 publications
(111 reference statements)
1
39
0
7
Order By: Relevance
“…This indicates that TL can improve EP by strengthening OC. Previous relevant study has revealed that TL plays a significant role in stimulating OC such as cooperation and adaptation to uncertain conditions (Lasrado and Kassem, 2021), which ultimately provides a higher level of performance (Maamari and Saheb, 2018). Finally, as hypothesized, OC also mediates the influence of leader's PSs on EP.…”
Section: Discussionmentioning
confidence: 70%
See 1 more Smart Citation
“…This indicates that TL can improve EP by strengthening OC. Previous relevant study has revealed that TL plays a significant role in stimulating OC such as cooperation and adaptation to uncertain conditions (Lasrado and Kassem, 2021), which ultimately provides a higher level of performance (Maamari and Saheb, 2018). Finally, as hypothesized, OC also mediates the influence of leader's PSs on EP.…”
Section: Discussionmentioning
confidence: 70%
“…One of the most crucial implications is that to encourage high EP in the tourism sector, leaders must strengthen OC, such as adaptive, collaborative, flexible, and team oriented. In addition, OC has a strong correlation with EP (Hogan and Coote, 2014;Lasrado and Kassem, 2021). OC can mediate the relationship of leader's PSs and EP.…”
Section: Discussionmentioning
confidence: 93%
“…Secondly, the research examines the mediating effect of adaptive culture on the relationship between transformational leadership and international intrapreneurship (Farrukh et al, 2021). The article emphasizes the fact that intrapreneurship behaviours of employees may translate into firm-level behaviours when organizational factors such as entrepreneurial orientation within the family firm or a pro-innovation culture, tolerance for experimentation and risk-taking, extended autonomy and access to resources for intrapreneur teams all influence these behaviours (Costanza et al, 2016;Laforet, 2016;Lasrado and Kassem, 2021). Transformational leaders are more effective when their employees and organizational culture are adaptable and receptive to change (Jocic et al, 2021;Khedhaouria et al, 2020;Verdu-Jover et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…2.7 Mediating role of adaptive culture in the relationship between transformational leadership and employee intrapreneurial behaviour Transformational leadership may use organizational factors as mediating mechanisms to promote employee intrapreneurial behaviour (Amankwaa et al, 2019;Chang et al, 2017;Lei et al, 2020;Moriano et al, 2014;Shafi et al, 2020;Yariv and Galit, 2017). Corporate culture is a critical antecedent and mediator, interacting with other organizational components to produce firm outcomes such as corporate entrepreneurship (Afsar and Umrani, 2019;Al-Ali et al, 2017;Do and Luu, 2020;Lasrado and Kassem, 2021). The effectiveness of a leader's behaviour is contingent upon the organizational culture (Golden and Shriner, 2019).…”
Section: Employee Psychological Empowerment and Employee Intrapreneurial Behaviourmentioning
confidence: 99%
“…Yönetim faaliyetin ana aktörü olan lider, örgütlerde kapsayıcı örgüt kültürünün oluşmasında önemli bir rol oynayabilir. Nitekim birikmiş ampirik literatür, liderin örgüt içerisinde önemli bir konumda olduğunu ve örgüt kültürünün oluşmasında kritik bir rol üstlendiğine vurgu yapmaktadır (Lasrado, 2020;Yıldız ve Ekingen, 2020). Örgütlerin insan sermayesindeki çeşitliliği, örgüt kültürünü değiştirmiş ve buna paralel olarak da liderlik davranışlarının değişimi zorunlu hale gelmiştir (Kuknor ve Bhattacharya, 2020).…”
Section: Introductionunclassified